The Musical Emotion Discrimination Task: A New Measure for Assessing the Ability to Discriminate Emotions in Music - MacGregor, Chloe; Müllensiefen, Daniel (Frontiers in Psychology, 2019)
Previous research has shown that levels of musical training and emotional engagement with music are associated with an individual’s ability to decode the intended emotional expression from a music performance. The present study aimed to assess traits and abilities that might influence emotion recognition, and to create a new test of emotion discrimination ability. The first experiment investigated musical features that influenced the difficulty of the stimulus items (length, type of melody, instrument, target-/comparison emotion) to inform the creation of a short test of emotion discrimination. The second experiment assessed the contribution of individual differences measures of emotional and musical abilities as well as psychoacoustic abilities. Finally, the third experiment established the validity of the new test against other measures currently used to assess similar abilities. Performance on the Musical Emotion Discrimination Task (MEDT) was significantly associated with high levels of self-reported emotional intelligence and emotional engagement with music as well as with performance on a facial emotion recognition task. Results are discussed in the context of a process model for emotion discrimination in music and psychometric properties of the MEDT are provided. The MEDT is freely available for research use.